2024
DOI: 10.1002/joa3.13030
|View full text |Cite
|
Sign up to set email alerts
|

The association between hyperuricemia and atrial fibrillation recurrence after catheter ablation

Hirotsuna Oseto,
Seigo Yamashita,
Michifumi Tokuda
et al.

Abstract: BackgroundHyperuricemia (HU) has been reported to be associated with a high incidence of atrial fibrillation (AF). However, the relationship between HUA and recurrent AF after catheter ablation (CA) is unclear.MethodsFour hundred consecutive AF patients (paroxysmal/persistent AF [PAF/PsAF]: 200/200) who underwent the initial CA were retrospectively enrolled. HU was defined as serum uric acid (SUA) level >7.0 mg/dL. We measured SUA levels 1 day before (pre‐CA) and 1 month after CA (post‐CA). A second‐generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…4 The results of previous studies support that increased uric acid level plays EDITORIAL an active role in the mechanism of atrial remodeling and AF rather than being an innocent bystander. Although the relation of preablation SUA levels alone with AF recurrence after catheter ablation was assessed in previous studies, Oseto et al 1 evaluated the association of serial SUA levels (preablation, post-ablation 1st, 3rd, and 6th months) with AF recurrence after catheter ablation. Only postablation SUA levels rather than preablation SUA levels were found as an independent predictor of AF recurrence after catheter ablation in PeAF patients.…”
Section: Editorial To "The Association Between Hyperuricemia and Atri...mentioning
confidence: 99%
See 1 more Smart Citation
“…4 The results of previous studies support that increased uric acid level plays EDITORIAL an active role in the mechanism of atrial remodeling and AF rather than being an innocent bystander. Although the relation of preablation SUA levels alone with AF recurrence after catheter ablation was assessed in previous studies, Oseto et al 1 evaluated the association of serial SUA levels (preablation, post-ablation 1st, 3rd, and 6th months) with AF recurrence after catheter ablation. Only postablation SUA levels rather than preablation SUA levels were found as an independent predictor of AF recurrence after catheter ablation in PeAF patients.…”
Section: Editorial To "The Association Between Hyperuricemia and Atri...mentioning
confidence: 99%
“…Only postablation SUA levels rather than preablation SUA levels were found as an independent predictor of AF recurrence after catheter ablation in PeAF patients. Oseto et al 1 showed that post-ablation reduction of the HU rates in PeAF patients was independent of the SUA-lowering medication rates. In parallel to this finding of Oseto et al, Aoyama et al 5 also showed a significant post-ablation reduction in SUA levels independent from inflammatory parameters and kidney functions at 12-month follow-up.…”
Section: Editorial To "The Association Between Hyperuricemia and Atri...mentioning
confidence: 99%
“…Oseto and colleagues have demonstrated a significant elevation in serum uric acid levels among patients with persistent AF compared to those with paroxysmal AF. 1 Moreover, the presence of post‐ablation hyperuricemia has been associated with the recurrence of AF in patients with persistent AF. However, several concerns have been raised.…”
mentioning
confidence: 99%
“… 2 In the authors' study, both uric acid and γ‐glutamyl transpeptidase levels were elevated in patients with persistent AF. 1 Elevated γ‐glutamyl transpeptidase levels may be linked to alcohol consumption, which has been associated with the onset and recurrence of AF. 3 It is highly recommended to adjust for these potential confounders to accurately assess the impact of serum uric acid levels on AF recurrence.…”
mentioning
confidence: 99%
See 1 more Smart Citation